Observations of optically active turbulence in the planetary boundary layer by sodar at the Concordia astronomical observatory, Dome C, Antarctica - Petenko, I.; Argentini, S.; Pietroni, I.; Viola, A.; Mastrantonio, G.; Casasanta, G.; Aristidi, E.; Bouchez, G.; Agabi, A.; Bondoux, E. (Astronomy & Astrophysics, 2014)
International audience